Challenges to Imagining Jesus as a Jew - Cunningham, Philip A. (Studies in Christian-Jewish Relations, 2026)
This essay posits that many Christians today ﬁnd it diﬃcult to imagine Jesus living a thoroughly Jewish life, if it even occurs to them to try to do so, because certain patterns of thought about him became embedded in Christian culture and were passed down the generations to the present day. It explores this premise in four sections: (1) theologies that dehumanize Jesus—those that declare or suggest that Jesus was not really a human being or only treat that humanity generically, (2) contemptuous theologies—those that denigrate Judaism to assert the superiority of Christianity, (3) oppositional theologies—those that set Jesus apart from his fellow Jews by positing a fundamental antagonism between Jesus or Christians and late Second Temple Judaism or Judaism today, often based on caricatures of Judaism, and (4) unsettling new theological questions—that arise from taking Jesus’s Jewishness seriously that can consciously or unconsciously deter people from thinking too much about the Jew Jesus. The essay concludes by arguing that a crucial step in forming Christians’ imagination about the Jew Jesus is to follow through on the educational and homiletic principles that many churches have already articulated.